Cały ten zgiełk. O wczesnych reakcjach na uhonorowanie Olgi Tokarczuk Literacką Nagrodą Nobla - Dariusz Nowacki (Postscriptum Polonistyczne)
The paper discusses selected reactions to the Nobel Prize for Literature awarded to Olga Tokarczuk. The author focuses on the dispute about the legitimacy and justification of the Swedish Academy’s decision, highlighting the sceptical opinions, in some cases challenging the Academy’s members’ verdict. Referring to a book by James F. English on cultural prizes, the author recalls the role of public controversies as an essential tool of influencing the general public. He also compares the situation of two winners of the Nobel Prize in Literature (Olga Tokarczuk – for 2018, Peter Handke – for 2019), announced on the same day. Concluding, the author seeks to present the most important aspects of the dispute on the position and influence of Tokarczuk’s literary output.